MicroRNA-122: assessment of diagnostic significance in HDV infection - M. E. Khodjaeva; A. S. Khikmatullaeva; N. S. Ibadullaeva; M. A. Abdukadirova; K. E. Novak; E. V. Esaulenko (Журнал инфектологии, 2024)
Aim: To evaluate the diagnostic significance of the relationship between the level of microRNA-122 expression and liver fibrosis during HDV infection.Materials and methods. The expression of microRNA-122 was determined in 203 blood samples. Blood sampling was done from 53 patients with chronic viral hepatitis D, 49 patients with liver cirrhosis of HDV etiology, and 69 patients with newly diagnosed HBs antigenemia. The control group consisted of practically healthy individuals (n=32).Results. In patients with negative RNA HDV levels, the level of microRNA-122 in the blood serum was significantly higher than in samples with positive RNA HDV levels (14.0±2.8 2^-ΔΔCt and 1.6±0.17 2^-ΔΔCt) (p ˂ 0.005). Meanwhile, in healthy individuals, the expression of microRNA-122 was statistically significantly lower – 1.3±0.03 2^-ΔΔCt (p ˂ 0.005). Undetectable levels of HDV RNA in the serum were accompanied by a high HBV viral load and a significantly higher level of microRNA-122, which was 8.7 times higher than in the group of HDV RNA-positive patients (p<0.005). In patients with liver fibrosis F1, the expression of microRNA-122 was higher than in patients with liver fibrosis F2, F3, F4 (p = 0.0001). The lowest levels of microRNA-122 were observed in liver fibrosis F4. Conclusion. The expression level of microRNA-122 in blood serum during HDV infection decreases as liver fibrosis progresses. The development of cirrhosis is accompanied by a 3.7-fold drop in the level of microRNA-122 compared to the group of patients with chronic hepatitis D. MicroRNA-122 can be used in laboratory monitoring of patients with various stages of HDV infection as an indicator of the activity of the process, assessing the severity of liver damage and the rate of progression of liver fibrosis.> ˂ 0.005). In patients with liver fibrosis F1, the expression of microRNA-122 was higher than in patients with liver fibrosis F2, F3, F4 (p = 0.0001). The lowest levels of microRNA-122 were observed in liver fibrosis F4.Conclusion. The expression level of microRNA-122 in blood serum during HDV infection decreases as liver fibrosis progresses. The development of cirrhosis is accompanied by a 3.7-fold drop in the level of microRNA-122 compared to the group of patients with chronic hepatitis D. MicroRNA-122 can be used in laboratory monitoring of patients with various stages of HDV infection as an indicator of the activity of the process, assessing the severity of liver damage and the rate of progression of liver fibrosis.